Does the compensation gap between executives and staffs influence future firm performance? The moderating roles of managerial power and overconfidence - Ping Liu; Md Sajjad Hosain; Liyan Li (International Journal of Management and Economics, 2019)
The study aims at identifying the influence of interior pay gap between senior executives and ordinary employees on the organization's future performance for listed Chinese firms. In addition, two other moderator variables have been included in the study referring management power as the percentage of senior managers holding "A" category shares for more than one position. The other one is managerial overconfidence defined as the change in management holdings by themselves (managers) positively. The paper is based on secondary data extracted from China's 'A' listed companies in Shanghai and Shenzhen Stock Exchanges with a valid sample size of 1,189. After detailed analysis (Pearson correlation and regression) between the variables, it was found that there is a moderate positive relationship between the pay gap and firms' future performance. The results further indicate that management power and overconfidence weaken the relationship between pay gap and corporate performance. The authors hope that this empirical study can guide the academicians intending to further excavate in this relatively uncharted area as well as the corporate body and top managers who seek some guidelines to formulate an effective pay plan.
Keywords: M1; M14; 650; China; pay gap; performance; firm; managerial power; managerial overconfidence